HbA1c Association With Transaminase Levels in Type 2 Diabetes: Hubungan HbA1c dengan Tingkat Transaminase pada Diabetes Tipe 2 - Intan Dara Puspita; Syahrul Ardiansyah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Type 2 diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia and progressive multisystem complications, including hepatic involvement. Specific Background: Hemoglobin A1c represents long-term glycemic control, while serum glutamic oxaloacetic transaminase and serum glutamic pyruvic transaminase are widely used biomarkers of hepatocellular injury in clinical practice. Knowledge Gap: Despite routine use of these parameters, evidence describing their statistical relationship in type 2 diabetes mellitus patients remains limited, particularly in Indonesian clinical settings. Aims: This study aimed to analyze the correlation between HbA1c levels and SGOT and SGPT levels in patients with type 2 diabetes mellitus. Results: A quantitative analytical cross-sectional design was applied to 30 patients aged over 45 years. Kendall’s tau-b analysis demonstrated a significant positive correlation between HbA1c and SGOT (p=0.000; r=0.557) and between HbA1c and SGPT (p=0.018; r=0.317), indicating moderate and low correlation strengths, respectively. Novelty: This study provides empirical evidence linking long-term glycemic control indicators with liver enzyme alterations among type 2 diabetes mellitus patients in a hospital-based Indonesian population. Implications: The findings suggest that elevated HbA1c levels are associated with increased liver enzyme levels, supporting the integration of glycemic monitoring and liver function assessment in the comprehensive management of type 2 diabetes mellitus.Highlights: Long-term glycemic status showed a statistically significant relationship with hepatic enzyme levels. The association strength differed between transaminase parameters, with a stronger pattern observed for AST. Elevated biochemical markers indicated potential hepatic involvement among older diabetic patients. Keywords : Type 2 Diabetes Mellitus, HbA1c, SGOT, SGPT, Liver Function